URGENSI HIFZ AL-DĪN DALAM PENETAPAN HAK ASUH ANAK DI MALAYSIA: TINJAUAN MASLAHAH MURSALAH - Khairul, Mohd; Pramadani, Putrina Srimulya; Haj, Hakan Alfijar; Muhammad, Pauzi; Mursalin, Ayub (TAHKIM, 2025)
Instilling religious values in children is a primary responsibility of every Muslim parent. This is crucial because religious education will shape children's behavior and morals in accordance with Islamic teachings. In this context, attention to children's religious education applies not only to intact families but is also highly relevant in situations of parental divorce. Children of divorced couples often face psychological and social instability, making the instilling of religious values a crucial factor in maintaining balance in their lives. In Malaysia, child custody, or hadhanah, is regThis study aims to analyze hadhanah regulations in Malaysia with a focus on protecting children's religious values. This study uses a normative approach, namely an approach that examines the law based on applicable norms, and uses the theory of maslahah mursalah as the basis for analysis. This research method is library research, with data sources derived from various scientific works such as journals, books, theses, and dissertations. Based on the results of the study, it was found that judges in the Malaysian Sharia Court place religious aspects as the primary consideration in deciding hadhanah cases. This indicates that protecting a child's religion is seen as part of hifdz al-dīn (maintaining religion), which is included in the hajiyah level in the hierarchy of needs according to maqāṣid al-sharī‘ah. Thus, hadhanah regulations in Malaysia are in line with sharia principles that emphasize the welfare of the community.ulated by Islamic family law. One crucial aspect of this regulation is protecting the child's religious beliefs to ensure they remain in line with Islamic beliefs and teachings, particularly when one parent is of a different religion or does not consistently practice Islam. Key words: Hadhanah, protection, religion, children.